Composite diaphragm adapting to low temperature and preparation method thereof

By using a composite separator composed of polymer porous substrate and functional coating on the lithium battery separator, the use of tubular composite particles to improve lithium ion conductivity and reduce the interface impedance of the separator, the low conductivity and cyclic rate of lithium batteries in low temperature environments is solved. The poor performance problem achieves better low temperature adaptability and battery performance.

CN119401065APending Publication Date: 2025-02-07GUANGDONG ZHUO HIGH TECH MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411498807.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In low temperature environments, the lithium ion conductivity of the separator is low, the internal electrode-diaphragm interface impedance and charge transfer impedance of the battery are large, and the battery cycle rate performance is low.

Method used

A composite membrane composed of a polymer porous substrate and a functional coating is used. The functional coating contains tubular composite particles. The tubular composite particles are composed of tubular boehmite, hydroxymethylcellulose and lithium salts. Through these tubular composite particles, it is lithium. Ions provide migration channels, improve lithium ion conductivity and reduce diaphragm interface impedance.

Benefits of technology

In a low temperature environment, the lithium ion conductivity is improved, the interface impedance of the diaphragm is reduced, the circulation rate performance of the battery is improved, the liquid absorption and liquid retention ability of the electrolyte is enhanced, and the consumption of the electrolyte at low temperatures is slowed down.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119401065A_ABST
    Figure CN119401065A_ABST
Patent Text Reader

Abstract

The invention discloses a composite diaphragm adapting to low temperature, which comprises a base material and a functional coating, the functional coating is provided with tubular composite particles, and the tubular composite particles comprise tubular boehmite, hydroxymethyl cellulose and lithium salt; the preparation method comprises the following steps: mixing an aluminum salt, a template agent, deionized water, a lithium salt, a chelating agent, a pH regulator and hydroxymethyl cellulose, carrying out a hydrothermal reaction, cooling after the hydrothermal reaction is finished, washing with water, centrifuging, and drying to obtain the low-temperature-adaptive composite diaphragm. Tubular composite particles containing tubular boehmite, hydroxymethyl cellulose and lithium salt are obtained; mixing the tubular composite particles, deionized water, a dispersing agent, a binder and a wetting agent to obtain coating slurry; the tubular composite particles are used for providing channels for lithium ion migration, so that the lithium ion conductivity is improved, the interface impedance of the diaphragm is reduced, and the cycle rate performance of a battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery diaphragms, and in particular to a composite diaphragm adaptable to low temperatures and a preparation method thereof. Background Art

[0002] With the increasing replacement of new energy sources such as electronic products, electric vehicles, and energy storage, lithium-ion batteries have been more widely used in related fields due to their good safety performance, high specific energy and power density, and long charge and discharge cycle life.

[0003] Lithium batteries are mainly composed of four main materials: positive electrode materials, negative electrode materials, electrolytes, and diaphragms. The diaphragms isolate the positive and negative electrodes to prevent the two electrodes from directly contacting and short-circuiting. The diaphragms have micropores inside for lithium ions to pass through. However, in a low-temperature environment, the lithium ion conductivity of the diaphragm of traditional lithium batteries is low, the electrode-diaphragm interface impedance and charge transfer impedance inside the battery are large, and the battery cycle rate performance is low. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a composite diaphragm adaptable to low temperatures and a preparation method thereof, which utilizes tubular composite particles to provide channels for lithium ion migration, thereby increasing lithium ion conductivity, reducing diaphragm interface impedance, and improving battery cycle rate performance.

[0005] To achieve the above purpose, the present invention adopts the following technical solutions:

[0006] A composite diaphragm adaptable to low temperatures comprises a polymer porous substrate and a functional coating, wherein the functional coating is coated on at least one side surface of the polymer porous substrate, the functional coating has tubular composite particles, and the tubular composite particles comprise tubular boehmite, hydroxymethyl cellulose and lithium salt.

[0007] A composite diaphragm consisting of a polymer porous substrate and a functional coating coated on at least one side of the polymer porous substrate is provided, wherein the functional coating has tubular composite particles, and the tubular composite particles include tubular boehmite, hydroxymethyl cellulose and lithium salt. The tubular composite particles are used to provide a channel for lithium ion migration, and lithium ions pass through the channel under an electric potential, thereby shortening the lithium ion transfer path, improving lithium ion conductivity, and reducing the diaphragm interface impedance. The battery can maintain lithium ion conductivity in a low temperature environment, and the hydroxymethyl cellulose has good compatibility with the electrolyte, thereby improving the affinity of the functional coating with the electrolyte, enhancing the liquid absorption and retention capacity, slowing down the electrolyte consumption at low temperatures, and thus improving the battery cycle rate performance.

[0008] As a preferred embodiment, the mass ratio of the tubular boehmite, hydroxymethyl cellulose and lithium salt is (50-100): (0-20): (0-30).

[0009] As a preferred solution, the thickness of the functional coating is 1 μm to 5 μm.

[0010] As a preferred embodiment, the bulk density of the functional coating is 0.8 g / m 2 ~1.5g / m 2 .

[0011] As a preferred solution, the particle size D50 of the tubular composite particles is 5 μm to 20 μm.

[0012] A method for preparing a composite diaphragm adapted to low temperatures comprises the following steps:

[0013] S1, preparing tubular composite particles, wherein S1 comprises the following steps:

[0014] S1-1, mixing and stirring aluminum salt, template agent and deionized water to obtain dispersion A;

[0015] S1-2, mixing and stirring a lithium salt, a chelating agent, a pH adjuster, and deionized water to obtain a dispersion B;

[0016] S1-3, mixing and stirring the dispersion A, the dispersion B and the hydroxymethyl cellulose to obtain a blended liquid C;

[0017] S1-4, adding the blended liquid C into a reactor for hydrothermal reaction, cooling after the hydrothermal reaction, and then washing, centrifuging, and drying to obtain tubular composite particles containing tubular boehmite, hydroxymethyl cellulose, and lithium salt.

[0018] S2, preparing a slurry: mixing and stirring the tubular composite particles, deionized water, a dispersant, a binder and a wetting agent to obtain a coating slurry;

[0019] S3, preparing a diaphragm: coating the coating slurry onto the surface of a polymer porous substrate to form a functional coating, and after drying, obtaining a composite diaphragm consisting of the polymer porous substrate and the functional coating.

[0020] As a preferred solution, in S1-1, the aluminum salt is first dissolved in deionized water and stirred to obtain an aluminum salt solution, and then the template is added to the aluminum salt solution and stirred to obtain the dispersion A.

[0021] As a preferred embodiment, in S1-3, under continuous stirring, dispersion B is added dropwise to dispersion A to obtain dispersion AB, and then hydroxymethyl cellulose is added to dispersion AB to obtain the blended liquid C.

[0022] As a preferred solution, in S1-4, after the hydrothermal reaction is completed, it is naturally cooled to room temperature and aged at room temperature for 24 hours, and then washed, centrifuged and dried.

[0023] As a preferred solution, in S2, 15 to 45 parts of tubular composite particles, 30 to 60 parts of deionized water, 0.1 to 3 parts of dispersant, 2 to 10 parts of adhesive, and 0.1 to 3 parts of wetting agent are mixed and stirred to obtain the coating slurry with a solid content of 20% to 45%.

[0024] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, a composite diaphragm composed of a polymer porous substrate and a functional coating coated on at least one side of the polymer porous substrate is provided, wherein the functional coating has tubular composite particles, and the tubular composite particles include tubular boehmite, hydroxymethyl cellulose and lithium salt. The tubular composite particles are used to provide a channel for lithium ion migration, and lithium ions pass through the channel under electric potential, thereby shortening the lithium ion transfer path, improving lithium ion conductivity, and reducing the diaphragm interface impedance. The battery can maintain lithium ion conductivity in a low temperature environment. The hydroxymethyl cellulose has good compatibility with the electrolyte, thereby improving the affinity of the functional coating with the electrolyte, enhancing the liquid absorption and retention capacity, slowing down the electrolyte consumption at low temperatures, and improving the battery cycle rate performance.

[0025] In order to more clearly explain the structural features, technical means and specific purposes and functions achieved by the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments: BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the first electron microscope image of the composite diaphragm containing tubular composite particles prepared in Example 6 of the present invention;

[0027] Figure 2 Figure 1 A partial enlarged schematic diagram;

[0028] Figure 3 Figure 2 A partial enlarged schematic diagram is shown in the figure. DETAILED DESCRIPTION

[0029] The present invention discloses a composite diaphragm adaptable to low temperatures, comprising a polymer porous substrate and a functional coating, wherein the functional coating is coated on at least one side surface of the polymer porous substrate, the functional coating comprises tubular composite particles, a binder, a dispersant, and a wetting agent, the tubular composite particles comprise tubular boehmite, hydroxymethyl cellulose, and a lithium salt, wherein the lithium salt is randomly distributed on the tubular boehmite, specifically, the lithium salt is randomly distributed inside and on the outer surface of the tubular boehmite; when a lithium battery is charged and discharged, the potential difference causes lithium ions to gradually undergo redox reactions, and the lithium salt attached to the tubular boehmite also undergoes corresponding reactions, providing more lithium ions for the migration of lithium ions, thereby effectively reducing the impedance of lithium ion migration in a low temperature environment, maintaining lithium ion conductivity, and improving battery cell performance.

[0030] It should be noted that the tubular boehmite has channels in it, and the channels allow electrolyte to flow. Under electric potential, lithium ions in the electrolyte can migrate from the channels.

[0031] The mass ratio of the tubular boehmite, hydroxymethyl cellulose and lithium salt is (50-100):(0-20):(0-30).

[0032] The thickness of the functional coating is 1 μm to 5 μm.

[0033] The bulk density of the functional coating is 0.8 g / m 2 ~1.5g / m 2 Preferably, the functional coating has a bulk density of 1.0 g / m 2 ~1.3g / m 2 It should be pointed out that the bulk density in the present invention refers to the surface density of the functional coating at 1 μm.

[0034] The particle size D50 of the tubular composite particles is 5 μm to 20 μm.

[0035] The diameter of the tubular composite particles is 1 μm to 10 μm.

[0036] The aspect ratio of the tubular composite particles is 2-10.

[0037] The bulk density is 0.8g / m 2 ~1.5g / m 2 The composite membrane prepared by the functional coating and tubular composite particles with a particle size D50 of 5μm to 20μm, a tube diameter of 1μm to 10μm, and an aspect ratio of 2 to 10 can achieve an ion conductivity of 0.15S / cm to 0.25S / cm, which makes the lithium battery have good low temperature adaptability.

[0038] The polymer porous substrate is one or more of a polyethylene film, a polypropylene film and a polyolefin film.

[0039] The thickness of the polymer porous substrate is 3 μm to 25 μm.

[0040] A method for preparing a composite diaphragm adapted to low temperatures comprises the following steps:

[0041] S1, preparing tubular composite particles, wherein S1 comprises the following steps:

[0042] S1-1, mixing and stirring aluminum salt, template agent and deionized water to obtain dispersion A;

[0043] S1-2, mixing and stirring a lithium salt, a chelating agent, a pH adjuster, and deionized water to obtain a dispersion B;

[0044] S1-3, mixing and stirring the dispersion A, the dispersion B and the hydroxymethyl cellulose to obtain a blended liquid C;

[0045] S1-4, adding the blended liquid C into a reactor for hydrothermal reaction, cooling after the hydrothermal reaction, and then washing, centrifuging, and drying to obtain tubular composite particles containing tubular boehmite, hydroxymethyl cellulose, and lithium salt.

[0046] S2, preparing a slurry: mixing and stirring the tubular composite particles, deionized water, a dispersant, a binder and a wetting agent to obtain a coating slurry, specifically, mixing and stirring 15 to 45 parts of tubular composite particles, 30 to 60 parts of deionized water, 0.1 to 3 parts of a dispersant, 2 to 10 parts of a binder (40 wt%), and 0.1 to 3 parts of a wetting agent to obtain the coating slurry having a solid content of 20% to 45%;

[0047] S3, preparing a diaphragm: coating the coating slurry onto the surface of a polymer porous substrate to form a functional coating, and after drying, obtaining a composite diaphragm consisting of the polymer porous substrate and the functional coating, wherein the functional coating is obtained by one of dip coating, wire rod coating, and micro-gravure coating in sequence or multiple times.

[0048] In S1-1, at room temperature, the aluminum salt is first dissolved in deionized water and stirred to disperse to obtain an aluminum salt solution, and then the template is added to the aluminum salt solution and continuously stirred at a speed of 1000-2000 rpm to obtain the dispersion A; by first mixing the aluminum salt with deionized water to obtain an aluminum salt solution, and then adding the template to the aluminum salt solution and stirring, the template is more evenly dispersed in the aluminum salt solution, which is beneficial for the aluminum salt solution to fully adhere to the circumferential outer surface of the template, so that in the hydrothermal reaction, the aluminum salt can evenly and stably undergo a crystal phase transformation and form tubular boehmite along the template.

[0049] The aluminum salt is one of aluminum nitrate, aluminum chloride, aluminum silicate and aluminum sulfate.

[0050] The template agent is a fibrous template agent or a rod-shaped template agent. Specifically, the template agent is a fibrous polyethylene oxide.

[0051] The pH regulator is an acidic pH regulator, the dispersion B is acidic, the dispersion B or the acidic pH regulator can etch the template, the pH of the dispersion B is 3-5, and the acidic pH regulator is one or more of glacial acetic acid, citric acid, and oxalic acid; by using a fibrous template or a rod-shaped template and an acidic pH regulator, through a hydrothermal reaction, the aluminum salt is phase-changed to form boehmite attached to the side of the template, and the template is etched by the acidic dispersion B or the acidic pH regulator to obtain tubular boehmite. The hydrothermal reaction is combined with the template and the acid etching method, so that the synthesis method of the tubular boehmite is controllable, the production process is simple, the production cost is low, and the boehmite has a low Mohs hardness, and the membrane coating processing performance is more superior and easier.

[0052] In S1-2, at room temperature, a lithium salt is first dissolved in deionized water and stirred to obtain a lithium salt solution, and then a chelating agent and a pH adjuster are added to the lithium salt solution and stirred to obtain the dispersion B. Specifically, after the chelating agent and the pH adjuster are added to the lithium salt solution, stirring is continued for 2 hours to 6 hours to allow the chelating agent to fully contact with the hydrolyzed lithium ions; by continuously stirring for 2 hours to 6 hours, the chelating agent is fully contacted with the hydrolyzed lithium ions, so that the chelating agent and the hydrolyzed lithium ions are combined to form a stable metal lithium ion aqueous solution, and the chelating agent can enhance the affinity of the metal lithium ions and the inorganic material, so that the lithium salt can better compound with the generated tubular boehmite (inorganic material) in the hydrothermal reaction, and promote the uniform dispersion of lithium ions in the tubular boehmite.

[0053] The lithium salt is one or more of lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiODFB), lithium bis(oxalatoborate) (LiBOB), lithium bis(difluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate (LiBF4), and lithium hexafluoroarsenate (LiAsF6).

[0054] The chelating agent is one or more of ethylenediaminetetraacetic acid (EDTA), diethylenetriaminepentaacetic acid (DTPA), hydroxyethylidenediphosphonic acid (HEDP), aminotrimethylenephosphonic acid (ATMP), triethylenetetraaminehexamethylenephosphonic acid sodium salt (TETHMP).

[0055] In S1-3, under continuous stirring, dispersion B is added dropwise to dispersion A to obtain a stable homogeneous dispersion AB, and then hydroxymethyl cellulose is added to dispersion AB to obtain the blended liquid C.

[0056] In S1-4, after the hydrothermal reaction is completed, it is naturally cooled to room temperature and aged at room temperature for 24 hours, and then washed, centrifuged and dried. Deionized water is used for washing. The solid product obtained after centrifugation is dried at 60°C. The dried solid product is ground and dispersed for 10 minutes to 30 minutes to obtain the tubular composite particles containing tubular boehmite, hydroxymethyl cellulose and lithium salt.

[0057] In S1-4, the temperature of the hydrothermal reaction is 120°C to 220°C, preferably 140°C to 200°C, and the time of the hydrothermal reaction is 14h to 24h, preferably 16h to 20h.

[0058] The dispersant is one or more of polyacrylate, sodium dodecylbenzene sulfonate, polyoxyethylene stearate, dodecyl polyoxyethylene ether, and sodium polyphosphate.

[0059] The binder is one or more of poly(meth)acrylic acid, polymethyl(meth)acrylate, styrene-butadiene rubber, polyurethane, epoxy resin, polyvinyl alcohol, polyvinyl acetate, acrylic polymer and acrylonitrile polymer.

[0060] The wetting agent is a non-ionic active agent such as oxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, fluorine-containing polyoxyethylene ether, etc.

[0061] The tubular boehmite hydrothermal reaction formation principle of the present invention:

[0062] When fibrous polyethylene oxide (a linear polyether material) is added as a template to an aluminum salt solution, the aluminum salt solution adheres to the outer surface of the template. Under high temperature and high pressure, after a hydrothermal reaction, the aluminum salt undergoes a crystal phase transformation, forming a boehmite unit cell and gradually forming a boehmite crystal. As the reaction time increases, the boehmite crystal grows along the linear template to form a rod-like structure coated on the side of the template. Under an acidic regulator, the template is gradually etched by acid to eventually form a tubular boehmite. The hydrothermal reaction chemical equation of boehmite is: Al 3+ +OH - →AlOOH;

[0063] During the hydrothermal reaction formation process of tubular boehmite, lithium salt is randomly dispersed and attached to the tubular boehmite under the action of a chelating agent, and hydroxymethyl cellulose is co-blended with the tubular boehmite as a mixed phase to form tubular composite particles with multiple phases.

[0064] Example 1

[0065] S1. Preparation of tubular composite particles:

[0066] At room temperature, 100 g of aluminum nitrate was dissolved in 500 mL of deionized water, and then 5 g of polyethylene oxide was added as a template, and the mixture was stirred rapidly to allow the template to be evenly dispersed in the aluminum salt solution to obtain dispersion A.

[0067] 15 g of lithium hexafluoroarsenate was weighed and dissolved in 500 mL of deionized water (lithium salt ratio was 15%), and 0.5 g of chelating agent ethylenediaminetetraacetic acid and 0.5% of glacial acetic acid were added, and stirred continuously for 4 h at room temperature to allow the chelating agent and the electrolyzed metal lithium ions to fully adsorb and contact, to obtain a dispersion B with a pH of 3 to 5;

[0068] The dispersion B is slowly added dropwise to the dispersion A under stirring, and after the dispersion A and the dispersion B form a stable homogeneous phase, 5% hydroxymethyl cellulose is added to obtain a blended liquid C;

[0069] The blended liquid C was transferred to a hydrothermal reactor and kept reacting at a stable temperature of 120°C for 14 hours. After the reaction was completed, it was naturally cooled to room temperature and aged for 24 hours. The solid product was collected by centrifugal washing several times at a centrifugal speed of 10,000 rpm for 10 minutes. The solid product was placed in a forced air drying oven and dried at 60°C. After drying, the solid product was taken out and ground in a mortar for 10 to 30 minutes to finally obtain tubular composite particles.

[0070] S2. Preparation of slurry:

[0071] First, 5 parts of styrene-butadiene rubber (40 wt%) and 100 parts of deionized water were mixed to form a polymer glue solution, and then 35 parts of the tubular composite particles obtained in S1 were weighed and added to the polymer glue solution, and continuously stirred and dispersed at 1200 rpm for 90 min; then 0.1 parts of a polyacrylate dispersant and 0.2 parts of a fluorinated polyoxyethylene ether wetting agent were added, and the mixture was slowly stirred at 200 rpm for 60 min to finally obtain a water-based coating slurry containing tubular composite particles.

[0072] S3. Preparation of diaphragm

[0073] The coating slurry obtained in S2 is coated on the surface of commercial polyolefin (PE, PP) diaphragm by micro-gravure, the coating weight is 2.2g / m2~2.8g / m2, the coating thickness is about 2μm, the coating speed is 40m / min~90m / min, and it is dried and cured in an oven to obtain a surface-modified composite diaphragm containing tubular composite particles.

[0074] Example 2

[0075] The difference between it and Example 1 is that the amount of hydroxymethyl cellulose added in S1 is increased to 10%, and the hydrothermal reaction conditions are changed to 150° C. / 14 h.

[0076] Example 3

[0077] The difference between this and Example 2 is that no hydroxymethyl cellulose is added to S1 (addition amount 0%).

[0078] Example 4

[0079] The difference between it and Example 2 is that the amount of hydroxymethyl cellulose added in S1 is increased to 20%.

[0080] Example 5

[0081] The difference between it and Example 2 is that the amount of hydroxymethyl cellulose added in S1 is increased to 30%.

[0082] Example 6

[0083] The difference between it and Example 4 is that the hydrothermal reaction conditions are changed to 180° C. / 18 h.

[0084] Example 7

[0085] The difference between it and Example 4 is that the hydrothermal reaction conditions are changed to 180° C. / 24 h.

[0086] Example 8

[0087] The difference between it and Example 4 is that the hydrothermal reaction conditions are changed to 220° C. / 24 h.

[0088] Example 9

[0089] The difference between it and Example 4 is that the hydrothermal reaction conditions are changed to 240° C. / 24 h.

[0090] Example 10

[0091] The difference between this embodiment and Example 6 is that lithium hexafluoroarsenate (lithium salt content 0%) is not added to the dispersion B, and the hydrothermal reaction conditions are changed to 180° C. / 18 h.

[0092] Embodiment 11

[0093] The difference between this embodiment and Example 6 is that 30 g of lithium hexafluoroarsenate (lithium salt content 30%) is added to the dispersion B, and the hydrothermal reaction conditions are changed to 180° C. / 18 h.

[0094] Example 12

[0095] The difference between this embodiment and Example 6 is that 40 g of lithium hexafluoroarsenate (lithium salt content 40%) is added to the dispersion B, and the hydrothermal reaction conditions are changed to 180° C. / 18 h.

[0096] Comparative Example 1

[0097] A conventional amorphous boehmite (particle size D50≤1.0μm, D90≤2.5μm) was selected from the market, and the slurry was prepared and coated under the same conditions as in Example 3, and the coating surface density was kept in the same range of 3.0g / m 2 ~3.6g / m 2 .

[0098] Comparative Example 2

[0099] A commercially available fibrous boehmite containing no lithium salt and no co-doped cellulose was selected, and the slurry was prepared and coated under the same conditions as in Example 3, and the same coating surface density range of 2.2 to 2.8 g / m2 was maintained.

[0100] Performance characterization: (powder particle size distribution, film air permeability, liquid absorption rate, ionic conductivity, low temperature rate cycle performance)

[0101] 1. Characterization and analysis of tubular composite particles and coating membrane performance

[0102] (1) Particle size of tubular composite particles

[0103] The size of the obtained tubular composite particles was analyzed and characterized by a laser particle size analyzer (Malvern MS2000+MU-LF), wherein the test range was 0.02 μm to 2000 μm, the detection angle was 0 to 135°, and internal and external ultrasound was used for particle dispersion, with an external ultrasound intensity of 50 KHz, an ultrasound duration of 5 min, an internal ultrasound intensity of 15 KHz, and a refractive index of 10% to 20%.

[0104]

[0105]

[0106] Table 1 Particle size of tubular composite particles synthesized under different conditions in Examples 1 to 12 and Comparative Examples 1 and 2

[0107] As can be seen from Table 1, as the temperature of the hydrothermal reaction increases, the size of the tubular composite particles of Examples 1 to 9 gradually increases, because the increase in temperature promotes the contact between free ionic groups and provides corresponding energy for the growth of particle crystals. In Examples 2 to 5, the temperature and time of the hydrothermal reaction remain consistent, and only the amount of cellulose added is changed, which has little effect on the size of the tubular composite particles. Comparative Examples 6 to 9, under the same temperature conditions or reaction time, the size of the obtained tubular composite particles is also larger by changing the hydrothermal reaction time or reaction temperature. And in Comparative Examples 10 to 12, changing the amount of lithium salt added does not have much effect on the particle size of the tubular composite particles, and basically maintains the same level. As for the stacking performance of the material, as the size of the tubular composite particles increases, the proportion of the unit stacking of the material is smaller, so the material stacking specific gravity (bulk density) is also reduced accordingly.

[0108] (2) Comparison of air permeability and thermal shrinkage of coated diaphragms

[0109] The permeability of the coated membrane was tested by Asahi Chemical, and the effect of the tubular composite particle coating on the permeability of the membrane was compared between Examples 1 to 12 and Comparative Examples 1 and 2. The permeability test method is as follows: Take a coated membrane with a sample size of 100mm×100mm (MD×TD), and test it using a permeability meter for 5s. The shrinkage test method is as follows: Take the coated membranes of Examples 1 to 12 and Comparative Examples 1 and 2 for heat shrinkage test, the sample size is 100mm×100mm (MD×TD), MD is the longitudinal direction of the membrane, and TD is the transverse direction of the membrane.

[0110] Thermal shrinkage test temperature: 130°C / 1h. The test results are shown in Table 2.

[0111]

[0112]

[0113] Table 2 Comparison of air permeability and heat shrinkage of coated diaphragms of Examples 1 to 12 and Comparative Examples 1 and 2

[0114] It can be seen from Table 2 that the air permeability of the coated diaphragms obtained in Examples 1 to 9 changes from large to small. This is mainly because as the temperature and duration of the hydrothermal reaction increase, the particle size of the tubular composite particles gradually increases, and the too small particle size material is densely accumulated on the surface of the diaphragm, which is prone to pore blocking. It is related to the bulk density of the material as a whole, so the diaphragm air permeability is relatively large. As for the shrinkage rate of the diaphragm, the dense coating is beneficial to the thermal shrinkage performance of the diaphragm, so the shrinkage rate of the diaphragms in the corresponding Examples 1 to 9 changes from small to large. Compared with Comparative Examples 1 and 2, the air permeability or thermal shrinkage of the coated diaphragm is larger under the same coating surface density, which seriously affects the internal resistance and safety performance of the battery cell. Therefore, considering the comprehensive performance of the diaphragm, the air permeability and thermal shrinkage of the coated film obtained in Example 6 are excellent, which plays a good role in the ion conduction and safety performance of the battery.

[0115] (3) Comparison of liquid absorption rate of coated diaphragms

[0116] The liquid absorption rate of the diaphragm was calculated by weighing method, and the electrolyte retention per unit area of ​​the coated diaphragms of Examples 1 to 12 and Comparative Examples 1 and 2 was compared. The test method is as follows: a sample of coated diaphragm with a size of 100 mm × 100 mm (MD × TD) was weighed and recorded as m0, and then immersed in the electrolyte at room temperature for 24 hours, and then taken out and wiped off the electrolyte on the surface of the diaphragm and weighed and recorded as m1. The liquid absorption rate calculation formula is: x = (m1-m0) / m0, and the final test results are shown in Table 3.

[0117]

[0118]

[0119] Table 3 Comparison of liquid absorption rate of coated membranes of Examples 1 to 12 and Comparative Examples 1 and 2

[0120] As can be seen from Table 3, the coated separators obtained in Examples 1 to 12, as the proportion of cellulose added in the material increases, the coated separators absorb more electrolyte and have better affinity for the electrolyte. In Example 3, Comparative Example 1 and Comparative Example 2, there is no cellulose affinity agent, and the overall electrolyte absorption performance is worse, affecting the later cycle of the battery, and the performance is very likely to fail after the electrolyte is completely consumed.

[0121] (4) Diaphragm ion conductivity and low temperature cycle rate performance

[0122] The polymer separators of the above-mentioned Examples 1 to 12 and Comparative Examples 1 and 2 were used with lithium iron phosphate positive electrode sheets and graphite negative electrode sheets by adopting a winding process to prepare cylindrical lithium ion batteries, and a rate discharge cycle test was carried out at low temperature.

[0123] Rate charge and discharge cycle test: At a temperature of -20°C, the lithium-ion battery was charged at constant currents of 1.0C, 2.0C, and 3.0C, and then charged at constant voltage until the current was ≤0.05C, and then stopped charging and left for 30 minutes. Then it was discharged at a current of 1.0C: one charge and discharge cycle is one circle, and a total of 100 circles were tested. The capacity retention rate of the first 0 circles was 100%. The battery capacity retention rate of different circles was calculated, and the results are shown in Table 4.

[0124]

[0125] Table 4 Comparison of battery cycle capacity retention rate of ion conductivity of coated diaphragm obtained in different embodiments and comparative examples

[0126] It can be seen from Table 4 that no hydroxymethyl cellulose is added to S1 of Example 3 (addition amount 0%), and compared with Comparative Example 1, the diaphragm prepared by tubular boehmite in Example 3 has higher ionic conductivity than the diaphragm prepared by conventional amorphous boehmite in a low temperature environment. In Example 10, no lithium hexafluoroarsenate is added to the dispersion B (lithium salt content 0%), and compared with Comparative Example 2, the diaphragm containing hydroxymethyl cellulose in Example 10 has a higher battery capacity retention rate than the diaphragm not containing hydroxymethyl cellulose in a low temperature environment.

[0127]

[0128] Table 5 Physical properties of coated diaphragms obtained in different embodiments and comparative examples

[0129] In summary, the present invention provides a composite diaphragm composed of a polymer porous substrate and a functional coating coated on at least one side of the surface of the polymer porous substrate, wherein the functional coating has tubular composite particles, and the tubular composite particles include tubular boehmite, hydroxymethyl cellulose and lithium salt. The tubular composite particles are used to provide a channel for lithium ion migration, and lithium ions pass through the channel under electric potential, thereby shortening the lithium ion transfer path, improving lithium ion conductivity, and reducing the diaphragm interface impedance. The battery can maintain lithium ion conductivity in a low temperature environment, and the hydroxymethyl cellulose has good compatibility with the electrolyte, thereby improving the affinity of the functional coating with the electrolyte, enhancing the liquid absorption and retention capacity, slowing down the electrolyte consumption at low temperatures, and thus improving the battery cycle rate performance.

[0130] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Therefore, any modification, equivalent replacement, improvement, etc. made to the above embodiment based on the technical practice of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A composite diaphragm adapted to low temperatures, characterized in that: The invention comprises a polymer porous substrate and a functional coating, wherein the functional coating is coated on at least one side of the surface of the polymer porous substrate, and the functional coating has tubular composite particles, wherein the tubular composite particles comprise tubular boehmite, hydroxymethyl cellulose and lithium salt.

2. The low temperature-adaptable composite diaphragm according to claim 1, characterized in that: The mass ratio of the tubular boehmite, hydroxymethyl cellulose and lithium salt is (50-100):(0-20):(0-30).

3. The low temperature-adaptable composite diaphragm according to claim 1, characterized in that: The thickness of the functional coating is 1 μm to 5 μm.

4. The low temperature-adaptable composite diaphragm according to claim 1, characterized in that: The bulk density of the functional coating is 0.8 g / m 2 ~1.5g / m 2 .

5. The low temperature-adaptable composite diaphragm according to any one of claims 1 to 4, characterized in that: The particle size D50 of the tubular composite particles is 5 μm to 20 μm.

6. A method for preparing a composite diaphragm adapted to low temperatures, characterized in that: The following steps are involved: S1, preparing tubular composite particles, wherein S1 comprises the following steps: S1-1, mixing and stirring aluminum salt, template agent and deionized water to obtain dispersion A; S1-2, mixing and stirring a lithium salt, a chelating agent, a pH adjuster, and deionized water to obtain a dispersion B; S1-3, mixing and stirring the dispersion A, the dispersion B and the hydroxymethyl cellulose to obtain a blended liquid C; S1-4, adding the blended liquid C into a reactor for hydrothermal reaction, cooling after the hydrothermal reaction, and then washing, centrifuging, and drying to obtain tubular composite particles containing tubular boehmite, hydroxymethyl cellulose, and lithium salt. S2, preparing a slurry: mixing and stirring the tubular composite particles, deionized water, a dispersant, a binder and a wetting agent to obtain a coating slurry; S3, preparing a diaphragm: coating the coating slurry onto the surface of a polymer porous substrate to form a functional coating, and after drying, obtaining a composite diaphragm consisting of the polymer porous substrate and the functional coating.

7. The method for preparing a composite diaphragm adapted to low temperatures according to claim 6, characterized in that: In S1-1, the aluminum salt is first dissolved in deionized water and stirred to obtain an aluminum salt solution, and then the template is added to the aluminum salt solution and stirred to obtain the dispersion A.

8. The method for preparing a composite diaphragm adapted to low temperatures according to claim 6, characterized in that: In S1-3, under continuous stirring, dispersion B is added dropwise to dispersion A to obtain dispersion AB, and then hydroxymethyl cellulose is added to dispersion AB to obtain the blended liquid C.

9. The method for preparing a composite diaphragm adapted to low temperatures according to claim 6, characterized in that: In S1-4, after the hydrothermal reaction is completed, it is naturally cooled to room temperature and aged at room temperature for 24 hours, and then washed, centrifuged and dried.

10. The method for preparing a composite diaphragm adapted to low temperatures according to any one of claims 6 to 9, characterized in that: In S2, 15 to 45 parts of tubular composite particles, 30 to 60 parts of deionized water, 0.1 to 3 parts of a dispersant, 2 to 10 parts of a binder, and 0.1 to 3 parts of a wetting agent are mixed and stirred to obtain the coating slurry having a solid content of 20% to 45%.